Effects of irregular-shift work and physical activity on cardiovascular risk factors in truck drivers - Marqueze, Elaine Cristina; Ulhoa, Melissa Araujo; Moreno, Claudia Roberta de Castro (Revista de Saúde Pública, 2013)
OBJECTIVE: To analyze the putative effect of type of shift and its interaction with leisure-time physical activity on cardiovascular risk factors in truck drivers. METHODS: A cross-sectional study was undertaken on 57 male truck drivers working at a transportation company, of whom 31 worked irregular shifts and 26 worked on the day-shift. Participants recorded their physical activity using the International Physical Activity Questionnaire along with measurements of blood pressure, body mass index and waist-hip ratio. Participants also provided a fasting blood sample for analysis of lipid-related outcomes. Data were analyzed using a factorial model which was covariate-controlled for age, smoking, work demand, control at work and social support. RESULTS: Most of the irregular-shift and day-shift workers worked more than 8 hours per day (67.7% and 73.1%, respectively). The mean duration of experience working the irregular schedule was 15.7 years. Day-shift workers had never engaged in irregular-shift work and had been working as a truck driver for 10.8 years on average. The irregular-shift drivers had lower work demand but less control compared to day-shift drivers (p < 0.05). Moderately-active irregular-shift workers had higher systolic and diastolic arterial pressures (143.7 and 93.2 mmHg, respectively) than moderately-active day-shift workers (116 and 73.3 mmHg, respectively) (p < 0.05) as well as higher total cholesterol concentrations (232.1 and 145 mg/dl, respectively) (p = 0.01). Irrespective of their physical activity, irregular-shift drivers had higher total cholesterol and LDL-cholesterol concentrations (211.8 and 135.7 mg/dl, respectively) than day-shift workers (161.9 and 96.7 mg/dl, respectively (ANCOVA, p < 0.05). CONCLUSIONS: Truck drivers are exposed to cardiovascular risk factors due to the characteristics of the job, such as high work demand, long working hours and time in this profession, regardless of shift type or leisure-time physical activity.